الشاهد الشعري في كتاب : إعراب ثلاثين سورة من القرآن ، لابن خالويه رحمه الله - جمعا ودراسة - - دخان محمد (University of Eloued جامعة الوادي, 2024)
" كتاب « إعراب ثلاثين سورة من القرآن الكريم » للعلّامة أبي عبد الله بن خالويه الهمذانيّ – رحمه الله –، من الكتب النّافعة، جمع فيه مصنّفه العديد من القضايا اللّغويّة التي عالجها مستندا إلى الشّواهد الشّعرية. وقد قمت بدراسة تلك الشّواهد، وبيّنت منهجه في عرضها، متبعا في ذلك خطة أكاديمية مكونة من: مقدمة، ثم مدخل نظري؛ ذكرت فيه: ترجمة المؤلّف، والتّعريف بكتابه، ومفهوم الشّاهد الشّعري. ثم أعقبت ذلك بمبحثين؛ فالمبحث الأوّل: تطرقت فيه للعلاقة بين التّفسير اللّغوي ، والشّاهد الشّعري. أما المبحث الثّاني: فذكرت فيه طريقة ابن خالويه في عرض الشّواهد الشّعرية، وأهم المآخذ عليها. وفي الأخير، انتهى البحث بخاتمة ، تضمنّت ما توصلت إليه من نتائج، وتوصيّات. "The book ""I'raab of Thirty Surahs from the Holy Quran"" by the scholar Abu Abdullah Ibn Khalawaih al-Hamdani - may God have mercy on him - is one of the beneficial books. Its author compiled numerous linguistic issues that he addressed based on poetic evidence. I have studied these poetic examples and explained his methodology in presenting them, following an academic plan consisting: An introduction, then a theoretical preface in which I mentioned: the author's biography, an introduction to his book, and the concept of poetic evidence. Then I followed with two topics, which include the applied study. The first topic: I discussed the relationship between linguistic interpretation and poetic evidence. As for the second topic: I mentioned Ibn Khalawaih's method of presenting poetic evidence, and the most important criticisms of it. In the final section, the research was concluded with a closing chapter that contained a summary of the key results and findings that were reached, as well as suggestions and recommendations. "
Keywords: الشاهد الشعري – ابن خالويه – التفسير اللغوي - إعراب ثلاثين سورة من القرآن الكريم; poetic evidence - Ibn Khalawaih - Linguistic interpretation - I'raab of Thirty Surahs